Who is better in project planning?Generative artificial intelligence or project managers? - André Barcaui; André Monat (Project Leadership and Society, 2023)
This paper presents a comparative study of generative artificial intelligence (AI), specifically the GPT-4 model, and a human project manager in the context of a project plan development. The study's objective was to analyze the content and structure of a project plan prepared by this disruptive new technology and its human counterpart, focusing on the digital technology sector. Through a primarily qualitative methodology, the study scrutinizes critical aspects of each part of the project plan, including scope preparation, schedule development, cost estimation, resources evaluation, quality planning, stakeholder mapping, communication planning, and risk analysis. The results indicate unique strengths and weaknesses for both AI-generated and human-generated project plans, revealing them as complementary in the project planning process. It also emphasizes the continued importance of human expertise in refining AI outputs and harnessing the full potential of AI through the process known as prompt engineering. In conclusion, this study illustrates the potential synergy between human experience and AI in project planning, suggesting the careful integration of human and AI capabilities is key to developing robust and trustworthy project plans.